2014
DOI: 10.1016/s2352-3018(14)70021-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of potential responses to future high levels of transmitted HIV drug resistance in antiretroviral drug-naive populations beginning treatment: modelling study and economic analysis

Abstract: Summary Background With continued roll-out of antiretroviral therapy (ART) in resource-limited settings, evidence is emerging of increasing levels of transmitted drug-resistant HIV. We aimed to compare the effectiveness and cost-effectiveness of different potential public health responses to substantial levels of transmitted drug resistance. Methods We created a model of HIV transmission, progression, and the effects of ART, which accounted for resistance generation, transmission, and disappearance of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Good quality of antiretroviral drugs found in our study was consistent with other studies [2931]. However, other relevant issues that rose from previous findings in other studies such as storage conditions and their impact on quality of medications were not documented [2–5, 3234]. …”
Section: Discussionsupporting
confidence: 91%
“…Good quality of antiretroviral drugs found in our study was consistent with other studies [2931]. However, other relevant issues that rose from previous findings in other studies such as storage conditions and their impact on quality of medications were not documented [2–5, 3234]. …”
Section: Discussionsupporting
confidence: 91%
“…The main reasons for this is that cheaper drugs are more commonly used in the first-line regimen than in the following ART lines [18]. Indeed, various authors [6, 19] have shown that the most powerful determinant of ART cost was the line of ART.…”
Section: Discussionmentioning
confidence: 99%
“…However, in LMIC settings, models have produced conflicting results regarding the cost-effectiveness of SGRT (Levison et al, 2013; Phillips et al, 2014a; Phillips et al, 2014b; Rosen et al, 2011). Platforms that are more economical than SGRT may play a role in expanding access to genotypic drug resistance testing, which is currently limited or non-existent in most LMICs.…”
Section: Hiv-1 Drug Resistance Testingmentioning
confidence: 99%
“…To help achieve these goals, the World Health Organization (WHO) in 2016 recommended that all HIV-infected individuals should begin ART as soon after diagnosis as possible (Treat All) and that pre-exposure prophylaxis (PrEP) should be considered for persons at high risk of HIV infection (World Health Organization, 2016b). While the successful implementation of these recommendations will reduce the number of new HIV infections, the dramatic increase in ARV use will likely increase the prevalence of acquired drug resistance (ADR) in treated individuals and transmitted drug resistance (TDR) in newly infected individuals (Phillips et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%